Pralatrexate in patients with relapsed or refractory peripheral T-cell lymphoma: results from the pivotal PROPEL study - O'Connor, Owen A; Pro, Barbara; Pinter-Brown, Lauren; Bartlett, Nancy; Popplewell, Leslie; Coiffier, Bertrand; Lechowicz, Mary Jo; Savage, Kerry J; Shustov, Andrei R; Gisselbrecht, Christian; Jacobsen, Eric; Zinzani, Pier Luigi; et al. (Journal of clinical oncology, 2011)
Peripheral T-cell lymphoma (PTCL) is a poor prognosis subtype of non-Hodgkin's lymphoma with no accepted standard of care. This study evaluated the efficacy and tolerability of pralatrexate, a novel antifolate with promising activity. Patients with independently confirmed PTCL who progressed following ≥ 1 line of prior therapy received pralatrexate intravenously at 30 mg/m(2)/wk for 6 weeks in 7-week cycles. Primary assessment of response was made by independent central review using the International Workshop Criteria. The primary end point was overall response rate. Secondary end points included duration of response, progression-free survival (PFS), and overall survival (OS). Of 115 patients enrolled, 111 were treated with pralatrexate. The median number of prior systemic therapies was three (range, 1 to 12). The response rate in 109 evaluable patients was 29% (32 of 109), including 12 complete responses (11%) and 20 partial responses (18%), with a median DoR of 10.1 months. Median PFS and OS were 3.5 and 14.5 months, respectively. The most common grade 3/4 adverse events were thrombocytopenia (32%), mucositis (22%), neutropenia (22%), and anemia (18%). To our knowledge, PROPEL (Pralatrexate in Patients with Relapsed or Refractory Peripheral T-Cell Lymphoma) is the largest prospective study conducted in patients with relapsed or refractory PTCL. Pralatrexate induced durable responses in relapsed or refractory PTCL irrespective of age, histologic subtypes, amount of prior therapy, prior methotrexate, and prior autologous stem-cell transplant. These data formed the basis for the US Food and Drug Administration approval of pralatrexate, the first drug approved for this disease.